2021
DOI: 10.1097/aln.0000000000003837
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacotherapy for the Prevention of Chronic Pain after Surgery in Adults: An Updated Systematic Review and Meta-analysis

Abstract: Background Chronic postsurgical pain can severely impair patient health and quality of life. This systematic review update evaluated the effectiveness of systemic drugs to prevent chronic postsurgical pain. Methods The authors included double-blind, placebo-controlled, randomized controlled trials including adults that evaluated perioperative systemic drugs. Studies that evaluated same drug(s) administered similarly were pool… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
84
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(90 citation statements)
references
References 135 publications
(338 reference statements)
2
84
3
1
Order By: Relevance
“… 26 However, most recent evidence contradicts Chaparro’s findings. 27 Here, we could not demonstrate a significant difference in chronic pain after CRS-HIPEC surgery between those treated with and without ketamine. However, our analysis showed that 15.9% of the patients not receiving ketamine complained of chronic pain (at 12 months) in comparison to 4% in the ketamine group, suggesting a possible protective effect.…”
Section: Discussioncontrasting
confidence: 67%
“… 26 However, most recent evidence contradicts Chaparro’s findings. 27 Here, we could not demonstrate a significant difference in chronic pain after CRS-HIPEC surgery between those treated with and without ketamine. However, our analysis showed that 15.9% of the patients not receiving ketamine complained of chronic pain (at 12 months) in comparison to 4% in the ketamine group, suggesting a possible protective effect.…”
Section: Discussioncontrasting
confidence: 67%
“…This characteristic would imply that PGB might affect mechanisms involved not simply in the transmission of nociceptive signals but rather in the CNS mechanism underlying the establishment of chronic pain through nociplastic mechanisms ( Fehrenbacher et al, 2003 , Tanabe et al, 2008 ). In support of this, the appearance of the analgesic effect of PGB is latent in patients with chronic pain ( Carley et al, 2021 ). Such particularity of the PGB effect should be considered to understand the mechanism of its analgesic effect in animal models and human patients with persistent chronic pain.…”
Section: Introductionmentioning
confidence: 88%
“…Furthermore, the absence of the analgesic effect of PGB in mice with an α 2 δ 1 subunit variant lacking binding affinity to PGB has supported the notion that α 2 δ 1 subunit is the central target of gabapentinoid analgesics ( Field et al, 2006 , Patel and Dickenson, 2016 ). Notably, it is well established that PGB has a potent analgesic effect on chronic sustained pain while its effect on acute pain is limited ( Carley et al, 2021 ). This characteristic would imply that PGB might affect mechanisms involved not simply in the transmission of nociceptive signals but rather in the CNS mechanism underlying the establishment of chronic pain through nociplastic mechanisms ( Fehrenbacher et al, 2003 , Tanabe et al, 2008 ).…”
Section: Introductionmentioning
confidence: 99%
“…Prevention of persistent postsurgical pain (PPP) is currently a priority for perioperative medicine (Glare et al, 2019;Katz et al, 2015;Kehlet et al, 2006). Evidence from randomized clinical trials (RCTs) suggests that perioperative pharmacological and regional anesthetic interventions may modestly reduce PPP risk (Carley et al, 2021;Weinstein et al, 2018). Since PPP is estimated to affect 10%-50% of the surgical population, even small-to-modest reductions in prevalence have the potential to improve the quality of life for many patients.…”
Section: Introductionmentioning
confidence: 99%